Ward round template: enhancing patient safety on ward rounds - Gilliland, Niall (BMJ Open Qual, 2018)
INTRODUCTION AND AIMS: Concerns had been raised at clinical governance regarding the safety of our inpatient ward rounds with particular reference to: documentation of clinical observations and National Early Warning Score (NEWS), compliance with Trust guidance for venous thromboembolism (VTE) risk assessment, antibiotic stewardship, palliative care and treatment escalation plans (TEP). This quality improvement project was conceived to ensure these parameters were considered and documented during the ward round, thereby improving patient care and safety. These parameters were based on Trust patient safety guidance and CQUIN targets. METHOD: The quality improvement technique of plan–do–study–act (PDSA) was used in this project. We retrospectively reviewed ward round entries to record baseline measurements, based on the above described parameters, prior to making any changes. Following this, the change applied was the introduction of a ward round template to include the highlighted important baseline parameters. Monthly PDSA cycles are performed, and baseline measurements are re-examined, then relevant changes were made to the ward round template. SUMMARY OF RESULTS: Documentation of baseline measurements was poor prior to introduction of the ward round template; this improved significantly following introduction of a standardised ward round template. Following three cycles, documentation of VTE risk assessments increased from 14% to 92%. Antibiotic stewardship documentation went from 0% to 100%. Use of the TEP form went from 29% to 78%. CONCLUSIONS: Following introduction of the ward round template, compliance improved significantly in all safety parameters. Important safety measures being discussed on ward rounds will lead to enhanced patient safety and will improve compliance to Trust guidance and comissioning for quality and innovation (CQUIN) targets. Ongoing change implementation will focus on improving compliance with usage of the template on all urology ward rounds.